Causal relationship between gut microbiota and constipation: a bidirectional Mendelian randomization study - Feng, Cuncheng; Gao, Guanzhuang; Wu, Kai; Weng, Xiaoqi (Frontiers in Microbiology, 2024)
Background: Constipation is a prevalent gastrointestinal disorder affecting approximately 15% of the global population, leading to significant healthcare burdens. Emerging evidence suggests that gut microbiota plays a pivotal role in the pathogenesis of constipation, although causality remains uncertain due to potential confounding factors in observational studies. This study aims to clarify the causal relationships between gut microbiota and constipation using a bidirectional Mendelian Randomization (MR) approach, which helps to overcome confounding issues and reverse causality.Methods: Utilizing data from genome-wide association studies (GWAS) from the MiBioGen consortium and other sources, we identified genetic variants as instrumental variables (IVs) for 196 bacterial traits and constipation. These IVs were rigorously selected based on their association with the traits and absence of linkage with confounding factors. We applied several MR methods, including Inverse Variance Weighted (IVW), MR Egger, and MR-PRESSO, to examine the causal effects in both directions.Results: Our analysis revealed a significant causal relationship where specific bacterial taxa such as